Port wine, an established product a new market: A comparative analysis ofperceptions offirms and consumers - Ana Patricia Silva; Jo\~ao Rebelo (Wine Economics and Policy, 2019)
Port wine industry can be considered as a case study of the effects of globalization, expressed at diverse levels, such as changes in habits of consumption and lifestyles, that lead to a decrease of consumption rates in the last years. The aim of this paper is to understand how to reverse the downward trend, proposing guidelines to increase Port wine competitiveness in the market. Therefore, the core of this research is to compare perception of wine firms and consumers, regarding the actual image and consumption of Port wine. A qualitative approach was applied including In-depth interviews with the directors of companies (n=20) and two focus groups with young consumers (n=15). Data were transcribed verbatim and content analysed. Results showed convergence between perception of wine firms and consumers regarding Port wine needs to increase its competitiveness in the market. Three main dimensions emerged, as the most important areas to develop: 1) promotion; 2) product adaptation to the market and 3) focus on innovation, mostly regarding the sensory characteristics of beverage, the packaging and the communication to consumers. This study aims to contribute to the growing field of wine marketing, which in special Port wine lacks research.
Keywords: 330